2012
DOI: 10.2217/clp.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia-induced acute pancreatitis: clinical considerations

Abstract: Editorial"Severe hypertriglyceridemia is associated with increased risk of acute pancreatitis. The clinical manifestation and prognosis of hypertriglyceridemia-induced acute pancreatitis is not different from acute pancreatitis associated with other causes."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Different outcomes have also been reported in previous studies. It was reported that there was no difference in mortality between patients with HLAP and those with NHLAP by Navarro et al 16 It was suggested by Jiang et al 18 and Kostapanos et al 19 that the clinical manifestation and prognosis of HLAP are not different from those of NHLAP. But a higher mortality was reported in patients with HLAP by Deng et al, 20 and Baranyai et al 21 found that severe prognosis and local complications were more frequent in HLAP compared with NHLAP.…”
Section: Discussionmentioning
confidence: 91%
“…Different outcomes have also been reported in previous studies. It was reported that there was no difference in mortality between patients with HLAP and those with NHLAP by Navarro et al 16 It was suggested by Jiang et al 18 and Kostapanos et al 19 that the clinical manifestation and prognosis of HLAP are not different from those of NHLAP. But a higher mortality was reported in patients with HLAP by Deng et al, 20 and Baranyai et al 21 found that severe prognosis and local complications were more frequent in HLAP compared with NHLAP.…”
Section: Discussionmentioning
confidence: 91%
“…Secondary factors contributing to hypertriglyceridemia should be evaluated and treated as their prevention may reduce the risk for acute pancreatitis. Alcohol use should be decreased, tight glycemic control should be established, hypothyroidism should be treated, and lipid-lowering therapy with fibrates should be initiated (6,7,16). A multidisciplinary team is essential to treatment success in the transgender population and should include professionals familiar with both gender dysphoria and transgender hormone therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen therapy, whether as oral contraception or hormone replacement therapy in post-menopausal women, is a rare, yet well-documented, cause of acute pancreatitis with as many as 40 known reported cases. The presumed mechanism is estrogen-induced hypertriglyceridemia as most reported cases document triglyceride levels greater than 1,000 mg/dL (6). Levels of this magnitude are most commonly caused by primary or genetic defects in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations